Assessing the Composition and Diversity of the Australian Interest Group System. Issue 4 (6th March 2016) - Fraussen, Bert; Halpin, Darren
Abstract : Any democratic society requires mechanisms for citizens to have effective political voice. Clearly, political parties provide a key channel for expressing views and preferences. However, organised interests provide another important mechanism for such representation. A crucial question in this regard is whether the interest group system is capable of ensuring the representation of a variety of public and private interests. Resolving these debates requires data that map the terrain and also are attentive to organisational diversity. This article takes up this challenge through exploring the composition and diversity of the Australian system of organised interests, using a new data set based on the Directory of Australian Associations. This system‐level approach delivers important insights into the nature of the Australian interest group system, as well as provides a framework for subsequent work interpreting and contextualising advocacy activities of particular groups, or lobbying dynamics in specific policy domains. Abstract : Organised interests provide an important mechanism for representation. A crucial question is whether the interest group system is capable of ensuring the representation of a variety of public and private interests. This paper takes up this question through exploring the composition and diversity of the Australian system of organised interests.